1988
DOI: 10.1021/np50060a024
|View full text |Cite
|
Sign up to set email alerts
|

Australine, a Novel Pyrrolizidine Alkaloid Glucosidase Inhibitor from Castanospermum australe

Abstract: stitution pattern, has been isolated from seeds of Castanospermum australe and shown to be a potent and specific inhibitor of amyloglucosidase. The structure was established by a combination of spectroscopic and chemical techniques and confirmed by X-ray crystallography. Australine is the first pyrrolizidine alkaloid to be identified as a glycosidase inhibitor and is the third glucosidase inhibitor, together with the indolizidine alkaloids castanospermine [2] and 6-epicastanospermine [3], to be isolated from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(116 citation statements)
references
References 15 publications
6
108
0
2
Order By: Relevance
“…Of note, I. alba produces indolizidine alkaloids, compounds with a fused sixand five-membered ring containing a heterocyclic nitrogen and showing slight structural resemblance to PAs (Gourley et al, 1969;Ikhiri et al, 1987). In Castanospermum australe (Fabaceae), PAs co-occur with indolizidine alkaloids (Molyneux et al, 1988). Further research should reveal whether the HSS-like enzyme is involved in the biosynthesis of these compounds.…”
Section: Gain and Loss Of Hss-like Sequences Within The Convolvulaceaementioning
confidence: 99%
“…Of note, I. alba produces indolizidine alkaloids, compounds with a fused sixand five-membered ring containing a heterocyclic nitrogen and showing slight structural resemblance to PAs (Gourley et al, 1969;Ikhiri et al, 1987). In Castanospermum australe (Fabaceae), PAs co-occur with indolizidine alkaloids (Molyneux et al, 1988). Further research should reveal whether the HSS-like enzyme is involved in the biosynthesis of these compounds.…”
Section: Gain and Loss Of Hss-like Sequences Within The Convolvulaceaementioning
confidence: 99%
“…Base hydrolysis of 11 followed by ion-exchange chromatography gave 12 which was cyclized to the desired pyrrolizidine ring system under Mitsunobu conditions 12,19 in pyridine at 0 o C. The crude reaction mixture was then treated under hydrogenolysis conditions 12,13,20 and then peracetylation gave the pyrrolizidine-tetraacetate 15 in 23% over yield from 11. Scheme 2 outlines our attempted synthesis of australine (2). This synthesis required inversion of the stereochemistry at C-7 in the pyrrolo [1,2-c]oxazol-3-one 9.…”
Section: 17mentioning
confidence: 99%
“…1 In the same year its 7a-epimer, australine (2), was isolated from the seeds of Castanospermum australe. 2 Later reports described the isolation of other epimers of 2 from these seeds, including 1-epiaustraline…”
mentioning
confidence: 99%
“…In traditional medicine, the pods of the plant are reported as astringent [8] and In treatment of post pyrandial hyperglycemia in diabetic patients [9]. On literature survey it was found that the wood of Castanospermum australe contains castanogenin and bayogenin [10] whereas castanogenol from bark [11], castanospermine [12] and australine [13] from seed are reported. Saponins from the fresh leaves of Castanospermum australe have also been characterized [14,15].…”
Section: Introductionmentioning
confidence: 99%